Changes in behavior and quality of life in German young children during the COVID-19 pandemic-results from the COVID kids bavaria study - Hannah Schillok; Hannah Schillok; Michaela Coenen; Michaela Coenen; Eva A. Rehfuess; Eva A. Rehfuess; Pia H. Kuhlmann; Stefan Matl; Hannah Kindermann; Nicole Maison; Nicole Maison; Nicole Maison; et al. (Frontiers Media S.A., 2023)
IntroductionThe COVID-19 pandemic with its containment measures such as closures of schools and daycare facilities led to numerous restrictions in daily life, putting developmental opportunities and health-related quality of life in children at risk. However, studies show that not every family was impacted equally by the pandemic and that this exceptional health and societal situation reinforced pre-existing health inequalities among the vulnerable. Our study aimed at analyzing changes in behavior and health-related quality of life of children attending elementary schools and daycare facilities in Bavaria, Germany in spring 2021. We also sought to identify associated factors contributing to inequalities in quality of life.MethodsData from a multi-center, open cohort study ("COVID Kids Bavaria") conducted in 101 childcare facilities and 69 elementary schools across all electoral districts of Bavaria were analyzed. Children attending these educational settings (aged 3-10 years) were eligible for participation in a survey on changes in behavior and health-related quality of life. The KINDLR questionnaire (based on children's self-report and parental report) was administered about one year after the onset of the pandemic (spring 2021). Descriptive and logistic regression analyses and comparisons to pre-pandemic KiGGS (German Health Interview and Examination Survey for Children and Adolescents) data were undertaken.ResultsAmong respondents, a high percentage of parents reported changes in their children's eating and sleeping behavior, sports and outdoor activities as well as altered screen time. Health-related quality of life in KINDLR analyses compared to pre-pandemic population averages were lower in all age groups (for 3-6-year-old KINDLR-total score: COVID Kids Bavaria MD 74.78 ± 10.57 vs KiGGS data 80.0 ± 8.1; 7-10 years-old KINDLR-total score: COVID Kids Bavaria MD 73.88 ± 12.03 vs KiGGS data 79.30 ± 9.0). No significant differences were detected with regard to associated factors, namely type of institution, sex of the child, migration background, household size and parental education.ConclusionThese findings suggest a relevant impact of the COVID-19 pandemic on children's behavior and health-related quality of life one year after the onset of the pandemic. Further analyses in large-scale longitudinal studies are needed to determine the effects of specific pandemic or crisis associated factors contributing to health inequalities.